Migrant workers in western Europe and the United States - Power, Jonathan, 1941-; Garling, Marguerite; Hardman, Anna (Pergamon international library of science, technology, engineering, and social studies., 1979)
Migrant Workers in Western Europe and the United States discusses the state of job migration of Europeans and Americans. The geographical table showing the country of origin of the worker and the number of such workers are presented in the text. This table also provides a statistical record of the volume of people that migrated under the covered years. Such a table shows if there is a steady or fluctuating increase or decrease of migrant workers.